2022
DOI: 10.3390/biomedicines10020279
|View full text |Cite
|
Sign up to set email alerts
|

E-Selectin Is Associated with Daytime and 24-Hour Diastolic Blood Pressure Variability in Type 2 Diabetes

Abstract: E-selectin is an endothelial cell adhesion molecule involved in vascular inflammation. Elevated E-selectin has been reported in patients with high blood pressure and diabetes. Given the increasing clinical relevance of parameters derived from ambulatory blood pressure monitoring, further investigation of their relationships with E-selectin is of interest. In this study, we aimed to investigate the association between serum E-selectin, office blood pressure and 24 h ambulatory blood pressure parameters in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Current evidence suggests that hypertension is accompanied by a chronic pro-inflammatory state and that inflammation may play a role in both the development of hypertension and end organ damage. Ciobanu et al reported that a high serum E-selectin level, as an inflammatory marker, was associated with daytime and 24 h diastolic BP variability in patients with type 2 diabetes [58]. In Kayıkçıo glu et al's study, the CRP/albumin ratio was found to be significant in predicting non-dipper patients even in normotensive individuals, and inflammation was emphasized [59].…”
Section: Our Findings About Abpmmentioning
confidence: 96%
“…Current evidence suggests that hypertension is accompanied by a chronic pro-inflammatory state and that inflammation may play a role in both the development of hypertension and end organ damage. Ciobanu et al reported that a high serum E-selectin level, as an inflammatory marker, was associated with daytime and 24 h diastolic BP variability in patients with type 2 diabetes [58]. In Kayıkçıo glu et al's study, the CRP/albumin ratio was found to be significant in predicting non-dipper patients even in normotensive individuals, and inflammation was emphasized [59].…”
Section: Our Findings About Abpmmentioning
confidence: 96%